The kingdom and the glory for a theological genealogy of economy and government (Homo Sacer II, 2) - Agamben, Giorgio 1942-; Chiesa, Lorenzo; Mandarini, Matteo; Agamben, Giorgio 1942-; Agamben, Giorgio 1942- (Stanford, California Stanford University Press, 2011)
The two paradigms -- The mystery of the economy -- Being and acting -- The kingdom and the government -- The providential machine -- Archaeology and bureaucracy -- The power and the glory -- The archaeology of glory -- Appendix : The economy of the moderns -- The law and the miracle -- The invisible hand
The two paradigms -- The mystery of the economy -- Being and acting -- The kingdom and the government -- The providential machine -- Archaeology and bureaucracy -- The power and the glory -- The archaeology of glory -- Appendix : The economy of the moderns -- The law and the miracle -- The invisible hand.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion And Politics; Power (Philosophy); Political Science -- Philosophy